A systematic review and meta-analysis of psychosocial interventions for 6–12-year-old children who have been forcibly displaced - Trimboli, Concettina; Parsons, Lauren; Fleay, Caroline; Parsons, Dave; Buchanan, Angus (2021)
Background: Children who have been forcibly displaced are likely to experience psychosocial challenges given they may be dealing with past trauma and challenges of adapting to their new environment. Effective psychosocial interventions are needed to promote psychosocial wellbeing. Literature identifies the ages of 6–12 years (middle childhood), as key to addressing psychosocial development. To date, systematic reviews identifying effective psychosocial interventions for children have focused on adolescents.